Design and Development of Fashion E-Commerce Using the WDLC Model With the Scrum Method - Muhammad Ardiansyah; Jumilliono Pratama (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2022)
Through the internet, all can be connected to each other. Internet can be used with various benefits, especially as a means to do business. One activity that can be used as an example is the fashion business. By utilizing internet technology which is integrated into the fashion business business system, hereinafter referred to as e-commerce is the activity of buying and selling goods or transmitting funds/data through electronic networks, especially the internet through websites. To establish a business system with e-commerce website integration that can be used effectively and efficiently, and can be improved from time to time. There is a need for the right method to build it, namely the Scrum method with the WDLC (Web Development Life Cycle) model. The result of this scientific project is the establishment of an effective and efficient fashion e-commerce website.